A method for preparing sodium ion battery modified asphalt-based hard carbon material

By mixing the asphalt with the glucosate fundamentals, it inhibits its graphite process, prepares hardcocarbon materials with a highly disorderly structure, solves the problem of poor storage performance of sodium ion in the existing carbon material, realizes high ratio and the capacity and Cycle stability electrochemical performance.

CN117326544BActive Publication Date: 2025-01-24HARBIN INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311398447.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-26
Publication Date
2025-01-24
Estimated Expiration
2043-10-26

AI Technical Summary

Technical Problem

The existing carbon materials prepared with asphalt are highly graphitized, resulting in poor sodium ion storage performance.

Method used

By mixing asphalt with gluconate-based metal salts and performing low-temperature carbonization and high-temperature treatment, the graphitization process of the asphalt is inhibited and a hard carbon material with a highly disordered structure is formed.

Benefits of technology

Improve the electrochemical performance of sodium ion battery modifiers asphalt -based hard carbon materials, increase its capacity and cycle stability, and reduce production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117326544B_ABST
    Figure CN117326544B_ABST
Patent Text Reader

Abstract

A method for preparing a sodium ion battery modified asphalt-based hard carbon material, which relates to a method for preparing a hard carbon material. It aims to solve the technical problem that the existing carbon materials prepared with asphalt as raw material have a high degree of graphitization, resulting in poor sodium ion storage performance. This method: asphalt and gluconate-based metal salts are mixed evenly to obtain a raw carbon source; the raw carbon source is first treated at a low temperature of 350 to 550°C, and then at a high temperature of 1000 to 1400°C to obtain a sodium ion battery modified asphalt-based hard carbon material. The hard carbon material introduces a large number of closed pores in the carbon matrix as storage sites for sodium ions, thereby obtaining a carbon negative electrode material with a highly disordered structure. The initial specific capacity of the prepared sodium ion battery is 125 to 204 mAh g ‑1 , at 1Ag ‑1 The first-cycle coulombic efficiency under current density is 61% to 89%, and the capacity retention rate after 1,000 cycles is 50% to 90%, which can be used in the field of sodium ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a hard carbon material. Background Art

[0002] In recent years, problems such as lithium resource shortages and price increases have seriously hindered the further development of lithium-ion batteries, and sodium-ion batteries with low costs and higher safety have attracted more and more attention. However, since sodium ions are heavier than lithium ions and less electronegative than lithium, their energy density is lower than lithium, and the specific capacity of the whole battery is lower. In addition, sodium ions are larger in size and difficult to deintercalate, resulting in poor battery cycle performance. In view of the two shortcomings of sodium-ion batteries, electrode materials are the key to improving their energy density, voltage and cycle performance. Only by developing positive and negative electrode materials suitable for the stable deintercalation of sodium ions can the practical application of sodium-ion batteries be promoted.

[0003] At present, the negative electrode materials widely used in sodium-ion batteries are mainly two amorphous carbon materials: hard carbon and soft carbon. The precursor raw materials of hard carbon materials are generally biomass or artificial synthetic resins. The resulting products have many performance advantages such as high sodium storage capacity, low sodium storage voltage, and good cycle performance, but they are expensive and have low carbon yields. The precursor raw materials of soft carbon are usually low in cost, have a more ordered structure, fewer defects and shorter interlayer spacing, and their specific capacity is often lower than that of hard carbon. The carbon layer arrangement regularity of hard carbon materials is lower than that of soft carbon materials, and more micropores can be formed between their layers to facilitate the insertion and extraction of sodium ions. It is the current preferred negative electrode material for sodium-ion batteries. The current bottleneck of its industrialization is mainly the inability to find cheap precursor raw materials suitable for large-scale mass production, and there is a problem of low initial coulombic efficiency.

[0004] Asphalt is an abundant byproduct in the petroleum industry, easily available and inexpensive. It is mainly composed of polycyclic aromatic hydrocarbons and has a high carbon yield after pyrolysis. However, as a soft carbon precursor, direct pyrolysis of asphalt undergoes an uncontrollable molten carbonization process. The strong π-π interaction between the excess hydrogen in its molecules and the aromatic molecules leads to the formation of highly graphitized soft carbon with a small interlayer spacing. This highly ordered microstructure is not conducive to the reversible embedding and deintercalation of sodium ions, which ultimately leads to poor sodium ion storage performance. Summary of the invention

[0005] The present invention aims to solve the technical problem that the existing carbon materials prepared with asphalt as raw material have a high degree of graphitization, resulting in poor sodium ion storage performance, and provide a method for preparing a sodium ion battery modified asphalt-based hard carbon material.

[0006] The method for preparing the sodium ion battery modified asphalt-based hard carbon material of the present invention is carried out according to the following steps:

[0007] 1. Evenly mix the asphalt and the gluconate-based metal salt to obtain a raw carbon source; in this step, the gluconate-based metal salt can effectively inhibit the graphitization process of the asphalt, so that the carbon frame structure of the finally prepared asphalt-based hard carbon material is suitable for the deintercalation during the sodium ion transmission process;

[0008] 2. Place the original carbon source in a high-temperature furnace, heat it to 350-550°C in an argon atmosphere and keep it warm for 1-3 hours. The product is treated with acid washing and centrifugal washing to obtain a precursor. In this step, when the carbon source is preheated, the asphalt can be effectively carbonized and cracked to form a preliminary carbon skeleton. At the same time, the gluconate metal salt is pyrolyzed in this process to produce a large amount of oxygen, which consumes excess hydrogen in the asphalt molecules and delays the ordered transformation of the asphalt structure. The solid products produced during the pyrolysis process will introduce a large number of closed pores in the carbon matrix, providing more active sites for the deintercalation of sodium ions. Controlling the appropriate heating rate and insulation temperature can control the decomposition degree of the gluconate metal salt, thereby regulating the pore size and distribution in the carbon matrix.

[0009] 3. Place the precursor in a high temperature furnace, heat it to 1000-1400°C in an argon atmosphere and keep it at this temperature for 1-3 hours, and then cool it to obtain a sodium ion battery modified asphalt-based hard carbon material. The high temperature treatment in step 3 effectively converts the precursor into a hard carbon material with a highly disordered structure.

[0010] Preferably, the mass ratio of the gluconate metal salt to asphalt in step one is (1-2):1.

[0011] Preferably, the asphalt and the gluconate metal salt in step 1 are mixed by ball milling, manual grinding or dissolving and mixing in tetrahydrofuran.

[0012] Preferably, the gluconate metal salt described in step 1 is at least one of sodium gluconate, calcium gluconate, zinc gluconate, copper gluconate and magnesium gluconate. The gluconate metal salt is selected as a regulator of the asphalt structure. The thermal decomposition products of different gluconate metal salts have different inhibitory effects on the graphitization transformation process of the asphalt, and the amount, size and distribution of metal oxides in the raw material can be effectively regulated by regulating the ratio of asphalt to gluconate metal salt, thereby playing a role in regulating the amount, size and distribution of pores in the hard carbon material.

[0013] Preferably, the heating rate during heating in step 2 is 1-10° C. / min.

[0014] Preferably, the heating rate during heating in step three is 5-10° C. / min.

[0015] The preparation method of the sodium ion battery modified asphalt-based hard carbon material of the present invention is to mix gluconic acid-based metal salt with asphalt, and the solid particle product of the decomposition of the gluconic acid-based metal salt molecules during the low-temperature carbonization process is wrapped in the carbon layer of the asphalt carbon, leaving deep holes of uniform size inside the carbon layer after acid washing, and the carbon layer wrapped on the surface will form a special pore-rich structure during the high-temperature carbonization process. At the same time, during the high-temperature treatment of asphalt, increasing the cross-linking degree of the asphalt molecular chain and weakening or destroying the interaction between aromatic hydrocarbons in the asphalt can interfere with the graphitization of the asphalt and promote the transformation of the microstructure from soft carbon to hard carbon. In addition, the gluconic acid-based metal salt will release a large amount of oxygen during the thermal decomposition process and generate solid particles such as metal oxides, which consume excess hydrogen in the asphalt and prevent the graphitization transformation of the asphalt. At the same time, a large number of closed pores are introduced into the carbon matrix, thereby converting the microstructure of the asphalt-derived carbon from ordered graphite soft carbon to more disordered hard carbon, thereby greatly improving its electrochemical performance.

[0016] The present invention uses cheap and readily available asphalt as a carbon source, and optimizes the structural morphology of the asphalt-based carbon material by adding different gluconate-based metal salt regulators. The prepared sodium ion battery asphalt-based carbon material has a highly disordered structure. The modified asphalt-based carbon material has clearly shown a typical hard carbon structure, and has excellent electrochemical performance when used in sodium ion batteries. This method uses asphalt as a carbon source and gluconate-based metal salts as a structural regulator. The solid product generated during the carbonization process can effectively inhibit the graphitization of the asphalt structure, and introduces a large number of closed pores into the carbon matrix as storage sites for sodium ions, thereby obtaining a carbon negative electrode material with a highly disordered structure. The pore structure of the finally prepared asphalt-based hard carbon material is evenly distributed, and the size is suitable for the embedding and de-embedding behavior of sodium ions during the charging and discharging process. The sodium ion battery assembled with the obtained product has an initial specific capacity of 125 to 204 mAh g -1 , at 1Ag -1 The first cycle coulomb efficiency under current density is 61% to 89%, and the capacity retention rate after 1000 cycles is 50% to 90%, showing high capacity and high cycle stability. The preparation method of the present invention is simple, has low equipment requirements, reduces production costs, can realize industrial large-scale production, and the product can be used as a high-performance sodium ion battery negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 is a scanning electron microscope photograph of the original pitch-based carbon material prepared in Comparative Example 1;

[0018] Figure 2 is a scanning electron microscope photograph of the sodium ion battery modified asphalt-based hard carbon material prepared in Example 1;

[0019] Figure 3 is a scanning electron microscope photograph of the sodium ion battery modified asphalt-based hard carbon material prepared in Example 2;

[0020] Figure 4 is a scanning electron microscope photograph of the sodium ion battery modified asphalt-based hard carbon material prepared in Example 3;

[0021] Figure 5 is a scanning electron microscope photograph of the sodium ion battery modified asphalt-based hard carbon material prepared in Example 4;

[0022] Figure 6 is a scanning electron microscope photograph of the sodium ion battery modified asphalt-based hard carbon material prepared in Example 5;

[0023] Figure 7 is the XRD spectra of the original pitch-based carbon material prepared in Comparative Example 1 and the sodium ion battery modified pitch-based hard carbon material prepared in Examples 1 to 5;

[0024] Figure 8 It is a Raman spectrum of the original pitch-based carbon material prepared in Comparative Example 1 and the sodium ion battery modified pitch-based hard carbon material prepared in Examples 1 to 5;

[0025] Fig. 9 Scanning electron microscope photograph of the sodium ion battery modified asphalt-based hard carbon material prepared in Example 7. DETAILED DESCRIPTION

[0026] The beneficial effects of the present invention are verified by the following examples.

[0027] Example 1: The preparation method of the sodium ion battery modified asphalt-based hard carbon material of this example is carried out according to the following steps:

[0028] 1. Add 1.5g of asphalt and 1.5g of calcium gluconate into a mortar and grind them manually for 30 minutes to evenly mix the two to obtain a raw carbon source; in this step, calcium gluconate is used to effectively inhibit the graphitization process of asphalt, so that the carbon framework structure of the finally prepared asphalt-based hard carbon material is suitable for embedding and de-embedding during the sodium ion transmission process;

[0029] 2. Place the original carbon source in a high-temperature furnace, heat it to 450°C at a rate of 5°C / min under an argon atmosphere and keep it warm for 1 hour. The obtained product is pickled with a hydrochloric acid solution with a concentration of 1 mol / L, centrifuged and washed until the filtered water is pH neutral, dried and ground into fine powder to obtain a precursor. In this step, when the carbon source is preheated, the asphalt can be effectively carbonized and cracked to form a preliminary carbon skeleton. At the same time, calcium gluconate produces a large amount of oxygen during the pyrolysis process, which consumes excess hydrogen in the asphalt molecules and delays the ordered transformation of the asphalt structure. The solid products produced during the pyrolysis process will introduce a large number of closed pores in the carbon matrix, providing more active sites for the deintercalation of sodium ions. The heating rate and insulation temperature controlled in this embodiment can control the decomposition degree of calcium gluconate, thereby regulating the pore size and distribution in the carbon matrix.

[0030] 3. Place the precursor in a high temperature furnace, heat it to 1200°C at a heating rate of 10°C / min in an argon atmosphere and keep it at that temperature for 2 hours, cool it, and grind it into fine powder to obtain a sodium ion battery modified asphalt-based hard carbon material. In this step, the precursor is effectively converted into a hard carbon material with a highly disordered structure through high temperature treatment.

[0031] Example 2: This example is different from Example 1 in that the calcium gluconate in step one is replaced by sodium gluconate, and the rest is the same as Example 1, to obtain a sodium ion battery modified asphalt-based hard carbon material.

[0032] Example 3: This example is different from Example 1 in that calcium gluconate in step 1 is replaced by zinc gluconate, and the rest is the same as Example 1 to obtain a sodium ion battery modified asphalt-based hard carbon material.

[0033] Example 4: This example is different from Example 1 in that the calcium gluconate in step 1 is replaced by copper gluconate, and the rest is the same as Example 1 to obtain a sodium ion battery modified asphalt-based hard carbon material.

[0034] Example 5: This example is different from Example 1 in that the calcium gluconate in step 1 is replaced by magnesium gluconate, and the rest is the same as Example 1 to obtain a sodium ion battery modified asphalt-based hard carbon material.

[0035] Comparative Example 1: In this comparative example, the original asphalt is directly carbonized, and the specific steps are as follows: 1. The asphalt is placed in a high-temperature furnace, and the temperature is increased to 450°C at a rate of 5°C / min under an argon atmosphere and kept warm for 1 hour. The resulting product is pickled with a hydrochloric acid solution with a concentration of 1 mol / L, and then centrifuged and washed until the filtered water is pH neutral, and then dried and ground into fine powder to obtain a precursor; 2. The precursor is placed in a high-temperature furnace, and the temperature is increased to 1200°C at a rate of 10°C / min under an argon atmosphere and kept warm for 2 hours, cooled, and ground into fine powder to obtain a carbon material directly carbonized from the original asphalt.

[0036] The scanning electron microscope image of the carbon material directly carbonized from the original pitch is shown in Figure 1 As shown, from Figure 1 It can be seen that the internal structure of the carbon material is dense and non-porous.

[0037] The scanning electron microscope photo of the sodium ion battery modified asphalt-based hard carbon material prepared in Example 1 is as follows: Figure 2 As shown, from Figure 2 It can be seen that the hard carbon material modified by calcium gluconate has high structural stability and closed pores with uniform distribution and uniform pore size, so that it can always maintain a complete disordered structure during the battery cycle as a negative electrode material, and is not prone to structural collapse, which is beneficial to improving the cycle stability of the material.

[0038] The scanning electron microscope photo of the sodium ion battery modified asphalt-based hard carbon material prepared in Example 2 is as follows: Figure 3 As shown, from Figure 3 It can be seen that although the surface of the carbon layer contains a large number of dense pores, the pore sizes are different.

[0039] The scanning electron microscope photo of the sodium ion battery modified asphalt-based hard carbon material prepared in Example 3 is as follows: Figure 4 As shown, from Figure 4 It can be seen that there are fewer holes in the carbon layer and the pore size is larger.

[0040] The scanning electron microscope photo of the sodium ion battery modified asphalt-based hard carbon material prepared in Example 4 is as follows: Figure 5 As shown, from Figure 5 It can be seen that the holes on the surface of the carbon layer are large. This is because the solid products produced by the decomposition of the modifier have serious agglomeration, resulting in large and shallow holes on the surface of the carbon layer after pickling.

[0041] The scanning electron microscope photo of the sodium ion battery modified asphalt-based hard carbon material prepared in Example 5 is as follows: Figure 6 As shown, from Figure 6 It can be seen that the number of pores on the surface of the carbon layer in the carbon layer structure is small, the pore size is larger and more concentrated than that of other modified samples, and the surface of the carbon layer is rough and has many cracks.

[0042] Figure 7 XRD spectra of the original pitch-based carbon material and the hard carbon products modified by adding different gluconate metal salts in Examples 1 to 5. Figure 7 It can be seen that compared with the original asphalt directly subjected to high temperature carbonization, the asphalt-based carbon material with the addition of gluconate-based metal salts can be observed to have a significantly widened (002) peak and move to a smaller angle, indicating that its interlayer spacing is enlarged and the order of the carbon microstructure is reduced. From the XRD results, it can be seen that the modified asphalt-based carbon material has clearly shown a typical hard carbon structure, indicating that several materials have a significant regulatory effect on the formation of the disordered structure of asphalt.

[0043] Figure 8 The Raman spectra of the original pitch-based carbon material and the hard carbon products modified by adding different gluconate metal salts in Examples 1 to 5. Figure 8 It can be seen that after direct carbonization of the original asphalt, except for the 1345 cm -1 and 1590cm -1 In addition to the two characteristic peaks of carbon materials, at 2700cm -1The characteristic G' peak of graphite material also appeared at 1200℃, which indicates that the original asphalt has shown a significant tendency to graphitize after high-temperature carbonization at 1200℃, and the degree of ordered arrangement between carbon layers has increased. Such a soft carbon structure is not suitable for the storage of sodium ions due to the small interlayer spacing and thermodynamic factors. However, the characteristic G' peak of graphite did not appear in the several asphalt-based carbon materials modified by gluconate metal salts, indicating that the graphitization tendency of asphalt during high-temperature carbonization was significantly inhibited and the degree of order between carbon layers was reduced. The ratio of the D peak to the G peak intensity of the modified asphalt-based carbon materials from sodium gluconate, calcium gluconate, zinc gluconate, copper gluconate to magnesium gluconate is 0.85, 0.98, 0.86, 0.90 and 0.74, respectively, and the carbon product of direct carbonization of the original asphalt is 0.60. Modified asphalt-based carbon material I D / I G The significant increase in the value further confirms the inhibitory effect of gluconate-based metal salts on the ordering transformation of asphalt structure during high temperature, transforming the asphalt-based carbon material from a highly graphitized structure to a disordered hard carbon structure that is more suitable for sodium ion storage.

[0044] The original asphalt-based carbon material and the sodium ion battery modified asphalt-based hard carbon material prepared in Examples 1 to 5 were used as negative electrode materials to assemble half-cells, and the electrochemical performance of the asphalt-based carbon negative electrode materials modified by different gluconic acid-based metal salts was compared. To ensure sufficient sodium ions, the half-cell used a sodium metal disc as the counter electrode, and the electrolyte used a dimethyl ether (DME) solution of NaPF6 with a concentration of 1 mol / L. The electrolyte dosage was 160 μL, and the loading amount of the active material on the negative electrode was controlled to be 2 mg cm -2 The assembled battery is 1Ag -1 The comparison of 1000-cycle performance and rate performance under current density is shown in Table 1 and Table 2, respectively.

[0045] Table 1 Cycling performance of original pitch-based carbon materials and sodium ion battery modified pitch-based hard carbon materials prepared in Examples 1 to 5

[0046]

[0047] Table 2 Rate performance of original pitch-based carbon materials and sodium ion battery modified pitch-based hard carbon materials prepared in Examples 1 to 5

[0048]

[0049] As shown in Table 1, among several gluconate-based metal salts, calcium gluconate has the most excellent improvement effect on the performance of asphalt-based carbon materials. The asphalt carbon material modified by it has a highly disordered carbon structure, which greatly improves the specific capacity performance of the original asphalt. At the same time, the high structural stability and evenly distributed, uniformly pore-sized closed pores enable it to always maintain a complete disordered structure as a negative electrode material during the battery cycle, and it is not easy to collapse the structure. Even after 1,000 long cycles, it still has a high capacity retention rate, and can still maintain excellent specific capacity at high current density, with excellent comprehensive performance.

[0050] The sample modified with sodium gluconate prepared in Example 2 has a large number of dense pores on its carbon layer surface, but the pore sizes are different, which is not conducive to the reversible insertion and extraction process of sodium ions, resulting in limited improvement in its initial coulombic efficiency. In addition, due to the excessive aggregation of pores in the carbon layer, its structure is fragile, and the improvement effect on long cycle performance and specific capacity performance under high current is very limited.

[0051] The sample prepared in Example 3 using zinc gluconate as the structure regulator also has a slightly improved initial specific capacity compared to the unmodified sample. However, due to the small number of pores produced after acid washing, the improvement in specific capacity performance is very limited. In addition, the larger pore size makes the structure of the modified carbon material unstable, and the performance is relatively general at high current density.

[0052] The modified sample with copper gluconate prepared in Example 4 has the largest holes on the surface of the carbon layer among several groups of samples. The solid products produced by its decomposition may have serious agglomeration, resulting in large and shallow holes on the surface of the carbon layer after pickling. Such large-diameter holes are very unfavorable to the structural stability of the material. Even if it exhibits a large specific capacity at a low current density, it is easy to collapse the structure when it undergoes high-rate cycling. The improvement effect is relatively general compared with the calcium gluconate sample.

[0053] The sample prepared in Example 5 with the addition of magnesium gluconate also has a significant improvement effect on the asphalt structure, and also exhibits a higher specific capacity at a low current density. The initial coulombic efficiency is significantly improved compared to the original asphalt, but the structural stability is slightly inferior to that of calcium gluconate, and the capacity retention rate after a long cycle is not good.

[0054] Example 6: This example is to mix materials by ball milling. The difference between this example and Example 1 is that step one is replaced by the following operation: 1.5g of asphalt and 1.5g of calcium gluconate are weighed and added to a ball mill, 15mL of ethanol is added as a solvent, and after ball milling for 30 minutes, the ethanol is evaporated and removed, and then ground to obtain the original carbon source; the other steps and parameters are the same as in Example 1 to obtain a carbon material.

[0055] Example 7: This example is to dissolve the mixed material by tetrahydrofuran. The difference between this example and Example 1 is that step 1 is replaced by the following operation: 1.5g of asphalt is dissolved in 50mL of tetrahydrofuran, stirred for 1h until the asphalt is completely dissolved, and then 1.5g of calcium gluconate is added and stirred for 12h to mix the calcium gluconate and the asphalt evenly, and then the tetrahydrofuran is removed by evaporation, and the residual solid product is ground to obtain the original carbon source. The other steps and parameters are the same as in Example 1 to obtain the carbon material.

[0056] The scanning electron microscope photo of the carbon material prepared in Example 7 is as follows Fig. 9 As shown. Fig. 9 It can be seen that the product prepared by tetrahydrofuran dissolution and mixing in Example 7 presents a special vortex layer structure. In the preparation process, a tetrahydrofuran (THF) dissolution and mixing step is first introduced. Since asphalt can be dissolved in tetrahydrofuran, calcium gluconate is mixed with asphalt therein, and the dissolved asphalt molecules will be wrapped on the surface of calcium gluconate to form a coated carbon layer. The solid particle product of the decomposition of calcium gluconate molecules during the low-temperature carbonization process is wrapped in the carbon layer of asphalt carbon. After pickling, deep holes of uniform size are left inside the carbon layer, and the carbon layer wrapped on the surface will become a vortex layer carbon block with a solid structure during the high-temperature carbonization process, forming a special pore-rich layered structure, which is more conducive to the deintercalation process of sodium ions and is conducive to the improvement of electrochemical performance.

[0057] The carbon materials prepared in Examples 6 and 7 were subjected to electrochemical performance tests. The carbon materials were used as negative electrode materials to assemble half-cells, and the electrochemical performance differences of the asphalt-based carbon negative electrode materials prepared by different mixing methods were compared. To ensure sufficient sodium ions, the half-cell used a sodium metal disc as the counter electrode, and the electrolyte used a dimethyl ether (DME) solution of NaPF6 with a concentration of 1 mol / L. The electrolyte dosage was 160 μL, and the loading amount of the active material on the negative electrode was controlled to be 2 mg cm -2 The assembled battery is 1Ag -1 The 1000 cycle performance at the current density is shown in Table 3.

[0058] Table 3 Cyclic performance of carbon materials prepared in Examples 1, 6 and 7

[0059]

[0060] From the cycle performance of the asphalt-based carbon materials in Table 3, it can be seen that there are very significant differences under different mixing methods. The samples dissolved and mixed by THF solution have a special pore-rich vortex layer structure, and the pores in the carbon layer are evenly distributed. The pores left after acid washing are also uniform, which greatly reduces the agglomeration phenomenon between particles and makes the obtained pore size uniform. It will not be too dense and cause the carbon structure to be fragile and brittle, which is more conducive to the deintercalation process of sodium ions, showing better specific capacity and long cycle performance than the manually ground mixed samples. The ball-milled mixed samples are ground under strong mechanical force, and the carbon blocks are relatively fine, resulting in fewer pores on the surface of the carbon layer, and the initial specific capacity is lower than that of the manually ground samples. However, since calcium gluconate and asphalt are evenly mixed after ball milling, the size of the carbon blocks is relatively uniform, and it still has a good initial coulomb efficiency and capacity retention rate, and the long cycle performance is improved compared with the hand-milled mixed samples.

Claims

1. A method for preparing a sodium ion battery modified asphalt-based hard carbon material, characterized in that: The method proceeds as follows:

1. Evenly mix asphalt and calcium gluconate to obtain a raw carbon source; wherein the mass ratio of calcium gluconate to asphalt is (1-2):1; 2. Place the original carbon source in a high temperature furnace, heat it to 350-550 °C in an argon atmosphere and keep it warm for 1-3 h. The obtained product is treated with acid washing and centrifugal washing to obtain a precursor.

3. Place the precursor in a high-temperature furnace, heat it to 1000-1400 °C in an argon atmosphere and keep it warm for 1-3 h, then cool it to obtain a sodium ion battery modified asphalt-based hard carbon material.

2. The method for preparing a sodium ion battery modified asphalt-based hard carbon material according to claim 1, characterized in that: The asphalt and calcium gluconate described in step 1 are mixed by ball milling, manual grinding or dissolving and mixing in tetrahydrofuran.

3. The method for preparing a sodium ion battery modified asphalt-based hard carbon material according to claim 1, characterized in that: The heating rate during the heating in step 2 is 1 to 10 °C / min.

4. The method for preparing a sodium ion battery modified asphalt-based hard carbon material according to claim 1, characterized in that: The heating rate during the heating in step 3 is 5 to 10 °C / min.